KUALITAS PELAYANAN KARTU IDENTITAS ANAK DI KOTA SUKABUMI - Rudhiawan .; Djadja Saefullah (Scientia Regendi, 2022)
This research is motivated by the quality of Child Identity Card Services in Sukabumi City which has not been implemented properly. In accordance with the 1945 Constitution, article 28B paragraph (2) that every child has the right to continue to grow, live and develop, and is entitled to protection from violence. The formulation in this study is: How is the Quality of Child Identity Card Services in Sukabumi City? The results showed that: 1). The issuance of Child Identity Cards at the Population and Civil Registration Office of Sukabumi City has been carried out even though it has not been going well 2). The Publication Service of Child Identity Cards at the Population and Civil Registration Office of Sukabumi City has not been in accordance with Law no. 25 of 2009 concerning Public Services, article 10 paragraph (2) and article 39. In the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards, Child Identity Cards are official identities for proof of children who are less than 17 years old and unmarried . In accordance with Article 2 of the regulation, the issuance of Child Identity Cards aims to improve data collection, protection, and fulfillment of citizens' constitutional rights. The method used in this study is a qualitative research method, data collected through primary data and secondary data, data collection techniques through observation, interviews, and documentation, the sampling technique used is the sampling technique used is purposive sampling. Based on the results of the study, the services at the Sukabumi City Population Service Office related to Child Identity Card services were good in terms of the Quality Dimension, but in practice it was not good in terms of Tangibles, Reability, Responsiveness, Assurance, Empathy aspects, as well as the efforts that were made. carried out by the community applying for Child Identity Cards and the Regional Government in this case the Population and Civil Registration Office of Sukabumi City which makes better and quality services. Keywords: Service Quality.